2016
DOI: 10.1063/1.4959117
|View full text |Cite
|
Sign up to set email alerts
|

Detailed high-resolution three-dimensional simulations of OMEGA separated reactants inertial confinement fusion experiments

Abstract: We present results from the comparison of high-resolution three-dimensional (3D) simulations with data from the implosions of inertial confinement fusion capsules with separated reactants performed on the OMEGA laser facility. Each capsule, referred to as a “CD Mixcap,” is filled with tritium and has a polystyrene (CH) shell with a deuterated polystyrene (CD) layer whose burial depth is varied. In these implosions, fusion reactions between deuterium and tritium ions can occur only in the presence of atomic mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Under these conditions, on-target illumination nonuniformity better than 2% rms 33 is expected without any external perturbations applied. However, previous work has shown that a number of external asymmetry seeds, including unintended drive asymmetry, 11 unintended capsule misalignment (offset), 9,34 and the capsule stalk mount, [35][36][37] can be expected to modify this picture. The anticipated effect of these factors is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Under these conditions, on-target illumination nonuniformity better than 2% rms 33 is expected without any external perturbations applied. However, previous work has shown that a number of external asymmetry seeds, including unintended drive asymmetry, 11 unintended capsule misalignment (offset), 9,34 and the capsule stalk mount, [35][36][37] can be expected to modify this picture. The anticipated effect of these factors is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several different simulation tools were brought to bear on these experiments to interpret the results. These include 1D LILAC, 51 1D and 2D xRAGE, 36,52,53 3D ASTER, 9,10 and 3D Chimera, 54 with the latter initialized with 1D HYADES. 55 Results from each are briefly discussed below.…”
Section: Simulationsmentioning
confidence: 99%
See 3 more Smart Citations